Synthesis and Optical Characterization of Carbon Materials Produced with a Power-Tunable Cw Laser - Cordero-Carrasco, R (SPIE, 2025)
In the laser ablation technique, is generally preferred (but not limited) to use a pulsed laser. Specific material characteristics can be obtained by tuning the laser parameters (e.g. wavelength, pulse width, total shot number or laser fluence). However, in previous works, only a few number of fluences have been analyzed (mainly because it is an equipment limitation) in the synthesis of materials. In this manuscript, a wide-ranging characterization of laser fluence in the production of carbon materials is presented. It is proposed to use a butterfly laser diode with a wavelength of 976 nm, continuous-wave radiation, and tunable power (therefore, tunable fluence) tightly focused by a large numerical aperture (NA) microscope objective to irradiate the material and thus produce laser ablation in ambient air and at room temperature. The main advantage of this laser is that it has an absolute maximum power of 350 mW, so it is possible to study the ablated material (shape and transmittance). The characterization of carbon materials was performed using interferometric techniques. © 2025 SPIE.